Sulfur Dioxide Fumigation Maintained the Postharvest Quality of ‘Munage’ Grape by Activating Sulfur Metabolism - ZHENG Yige, XING Shijun, SHI Wenjian, YUAN Yuyao, WU Bin, ZHANG Zheng (Shipin Kexue, 2025)
Hydrogen sulfide (H2S) is a key intermediate in sulfur metabolism. In order to investigate the role of sulfur metabolism in the effect of sulfur dioxide (SO2) on maintaining the post-harvest quality of table grapes, as well as the potential function of H2S in this process, ‘Munage’ grapes (Vitis vinifera L.) were treated with 500 μL/L SO2 alone or in combination with 0.5 mmol/L DL-propargylglycine (PAG) as a H2S inhibitor. PAG was sprayed on grapes 24 h before harvest and distilled water was used as a control. Grapes were stored at (0 ± 1) ℃ and 80%–90% relative humidity. Fruit firmness, berry shatter, decay incidence, sulfur metabolites, enzymatic activities and gene expression levels were evaluated every 10 days, and correlation analysis was performed. The results showed that SO2 treatment maintained fruit firmness and inhibited the increase of berry shatter and decay incidence. At the end of storage, the fruit hardness of the SO2 treatment group was 36.9% higher than that of the control group, and the grain drop rate and decay rate were 70.5% and 83.7% lower than those of the control group, respectively. Additionally, SO2 promoted the accumulation of the sulfur metabolites SO32-, H2S, cysteine and glutathione (GSH), and improved the activities of sulfite reductase, serine acetyltransferase, O-acetylserine(thiol)lyase, D-cysteine desulftosylase, L-cysteine desulfhydrylase, cystathion β-synthase and 3-mercaptopyruvate sulfur transferase by up-regulating the expression of sulfur metabolism pathway-related genes. These indicated that SO2 had a positively regulatory effect on sulfur metabolism. Correlation analysis revealed that SO32-, H2S, and GSH were positively correlated with fruit firmness and negatively with shatter and decay rates. The combination of PAG and SO2 weakened the regulatory effect of SO2 on sulfur metabolism and thereby the preservation effect of SO2 by inhibiting the synthesis of H2S. In conclusion, SO2 can effectively maintain the postharvest quality of grapes by enhancing sulfur metabolism.